What do we know about the future of agri-food systems in Central and West Asia and North Africa (CWANA)? - Frija, Aymen (CGIAR, 2023)
Food, land, and water systems face daunting challenges in the future, and the body of research exploring these challenges is growing rapidly. This note is part of a series developed by the CGIAR Foresight Initiative to summarize what we know today about the future of various aspects of food systems. The goal of these notes is to serve as a quick reference, point to further information, and help guide future research and decisions. This note was prepared in collaboration with the CGIAR Initiative on Fragility to Resilience in Central and West Asia and North Africa.